Optimising position control of a solar parabolic trough - Puramanathan Naidoo; Theo van Niekerk (South African Journal of Science)
In today's climate of growing energy needs and increasing environmental concerns, alternatives to the use of non-renewable and polluting fossil fuels have to be investigated. One such alternative is solar energy. This study is based on the implementation of a mathematical computation - the PSA (Plataforma Solar de Almeria) computation developed at PSA (the European Test Centre for solar energy applications) - embedded in a control algorithm to locate the position of the sun. Tests were conducted on a solar parabolic trough (SPT) constructed at the Solar Thermal Applications Research Laboratory of the Mangosuthu University of Technology (Durban, South Africa) for optimal position control using the PSA value. The designed control algorithm embedded in an industrial Siemens S7-314 C-2PtP programmable logic controller compared the PSA computation to a measured position of the SPT to optimally rotate the SPT to a desired position with the constant movement of the sun. The two main angles of the sun relative to the position of the SPT on earth, the zenith angle and the azimuth angle, both calculated in the PSA from the vertical and horizontal planes, respectively, were applied to the control algorithm to generate an appropriate final tracking angle within a 0.007 radian (0° 24′ 3.6″) tolerance, in accordance to the construction specifications and solar collector testing standards of the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE, 1991). These values, together with the longitude and latitude applicable to the geographical location of the SPT, were processed in the control software to rotate the SPT to an optimal position with respect to the position of the sun in its daily path, for solar-to-thermal conversion.